2018
DOI: 10.14202/vetworld.2018.1371-1375
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar organizer region banding in crossbred and non-descript pigs of India

Abstract: Aim:The objective of this experiment was to study the nucleolar organizer region (NOR)-banding pattern in Large White Yorkshire (LWY) crossbred and non-descript pigs and finding differences in the number of NORs between animals and between genetic groups.Materials and Methods:The experiment was carried out on 15 females, and 15 males of LWY crossbred and non-descript pigs to study NOR-banding pattern by employing ammoniacal silver staining technique.Results:A total of 63 and 65 number of good metaphases were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The extra material that was detected by oligo-banding was on the p arm of SSC10 between the first probe and the centromere, and included a red-labelled fragment. Previous studies have revealed an active nucleolar organizer region (NOR) in this part of SSC10 [ 43 , 50 52 ]. Such regions contain repeated ribosomal gene clusters (rDNA) in tandem [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extra material that was detected by oligo-banding was on the p arm of SSC10 between the first probe and the centromere, and included a red-labelled fragment. Previous studies have revealed an active nucleolar organizer region (NOR) in this part of SSC10 [ 43 , 50 52 ]. Such regions contain repeated ribosomal gene clusters (rDNA) in tandem [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such regions contain repeated ribosomal gene clusters (rDNA) in tandem [ 53 ]. Considerable interspecies and intraspecies variability within rDNA has been reported previously [ 52 54 ], mainly in terms of cluster abundance and location [ 55 , 56 ]. Studies in Lolium spp .…”
Section: Discussionmentioning
confidence: 99%